Immobilization of a molecular cobalt electrocatalyst by hydrophobic interaction with a hematite photoanode for highly stable oxygen evolution. Issue 70 (27th July 2015) - Joya, Khurram S.; Morlanés, Natalia; Maloney, Edward; Rodionov, Valentin; Takanabe, Kazuhiro
Abstract : A highly stable performance was achieved during photoelectrochemical oxygen evolution using a molecular cobalt catalyst utilizing its hydrophobic nature. Abstract : A unique modification of a hematite photoanode with perfluorinated Co-phthalocyanine (CoFPc) by strong binding associated with hydrophobic interaction is demonstrated. The resultant molecular electrocatalyst – a hematite photoanode hybrid material showed a significant onset shift and high stability for the photoelectrochemical oxidation evolution reaction (OER).